2017
DOI: 10.1080/01635581.2017.1299878
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Undernutrition on the Pharmacokinetics and Pharmacodynamics of Anticancer Drugs: A Literature Review

Abstract: The etiology of undernourishment in cancer patients is multifactorial: tumor-related mechanisms (such as obstruction, metabolic abnormalities, and functionality changes) in addition to the influence of anticancer therapies, which can induce or worsen undernutrition. The evident role of undernutrition in cancer treatment outcomes suggests the need of considering nutritional status when evaluating anticancer drugs. In order to merge the available data and offer researchers and clinicians a global view of this ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…A total of 235 samples corresponding to 8.7 samples per patient were available for the analysis. A 2‐compartment model with linear elimination best described docetaxel PK, although a nonlinear distribution was observed in 3 patients as previously described 32 . Diagnostic plots (Figures 1 and 2) showed that the model had an overall good fit.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…A total of 235 samples corresponding to 8.7 samples per patient were available for the analysis. A 2‐compartment model with linear elimination best described docetaxel PK, although a nonlinear distribution was observed in 3 patients as previously described 32 . Diagnostic plots (Figures 1 and 2) showed that the model had an overall good fit.…”
Section: Resultssupporting
confidence: 66%
“…Although different population PK models of docetaxel were developed for metastatic breast cancer patients, here, we report for the first time a nonparametric population model that was successfully used as a clinical routine tool for dosing management based on drug exposure and the intended target in early breast cancer. Patients with advanced and metastatic tumours develop physio‐pathological changes previously reported and that may affect docetaxel PK–PD relationship 12,32,33 . Despite scarce data being reported, previous authors proposed systemic exposure targets for docetaxel; these values were based on clinical observations from patients with different types of tumours distinct from early breast cancer and without the development of a PK‐PD study as we developed in the present report 34–37 …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The presence of unsaturated lipid chains in cancer cell membranes confers negative charges that allow them bind with the positive charges present in cationic peptides, increasing the selectivity of these peptides for cancer cells (Chen et al 2014;Deslouches and Di 2017). Furthermore, anticancer cationic peptides have many features such as mild toxicity without accumulation in different tissues and eventually selectivity and specificity for cancer targets and receptors (Perez-Pitarch et al 2017). In this work, we focused on brain cancer cells, specifically in one representative lineage Differences in plasma membrane alterations ranging from membrane integrity maintenance (early stage) to the progressive membrane ruptures (middle-to-late stages) were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Low lean body mass was associated with the increased occurrence of chemotherapy-related toxicities [ 44 ]. The relationship between body composition and pharmacokinetics of chemotherapy is also well established [ 45 ]. Recently, Cereda et al demonstrated that muscle weakness was a better predictor of survival than skeletal muscle mass estimated by bioelectrical impedance analysis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%